Genome‐Wide Association Study of Liver Fat: The Multiethnic Cohort Adiposity Phenotype Study. Issue 8 (25th June 2020) - Park, S. Lani; Li, Yuqing; Sheng, Xin; Hom, Victor; Xia, Lucy; Zhao, Kechen; Pooler, Loreall; Setiawan, V. Wendy; Lim, Unhee; Monroe, Kristine R.; Wilkens, Lynne R.; Kristal, Bruce S.; et al.
Abstract : The global rise in fatty liver is a major public health problem. Thus, it is critical to identify both global and population‐specific genetic variants associated with liver fat. We conducted a genome‐wide association study (GWAS) of percent liver fat and nonalcoholic fatty liver disease (NAFLD) assessed by magnetic resonance imaging in 1, 709 participants from the population‐based Multiethnic Cohort Adiposity Phenotype Study. Our participants comprised older adults of five U.S. racial/ethnic groups: African Americans (n = 277), Japanese Americans (n = 424), Latinos (n = 348), Native Hawaiians (n = 274), and European Americans (n = 386). The established missense risk variant rs738409 located in patatin‐like phospholipase domain containing 3 ( PNPLA3 ) at 22q13 was confirmed to be associated with percent liver fat ( P  = 3.52 × 10 −15 ) but more strongly in women than men ( P heterogeneity = 0.002). Its frequency correlated with the prevalence of NAFLD across the five ethnic/racial groups. Rs738409 was also associated with homeostasis model assessment of insulin resistance (HOMA‐IR) (beta = 0.028; P  = 0.009) and circulating levels of insulin (beta = 0.022; P  = 0.020) and alanine aminotransferase (beta = 0.016; P  = 0.030). A novel association of percent liver fat with rs77249491 (located at 6q13 between limb region 1 domain containing 1 [ LMBRD1 ] and collagen type XIX alpha 1 chain [ COL19A1 ] ( P  = 1.42 × 10 −8 ) was also observed. Rs7724941 was associated with HOMA‐IR (beta = 0.12; P  = 0.0005), insulin (beta = 0.11; P  = 0.0003), triglycerides (beta = 0.059; P  = 0.01), high‐density lipoprotein (beta = −0.046; P  = 0.04), and sex hormone binding globulin (beta = −0.084; P  = 0.0012). This variant was present in Japanese Americans (minor allele frequency [MAF], 8%) and Native Hawaiians (MAF, 2%). Conclusion : We replicated the PNPLA3 rs738409 association in a multiethnic population and identified a novel liver fat risk variant in Japanese Americans and Native Hawaiians. GWASes of percent liver fat in East Asian and Oceanic populations are needed to replicate the rs77249491 association. Abstract : We conducted a genome‐wide association study of % liver fat and NAFLD assessed by magnetic resonance imaging (MRI) in 1, 709 participants from the population‐based Multiethnic Cohort‐Adiposity Phenotype Study (MEC‐APS), comprised of older adults of five US racial/ethnic groups: African Americans (n = 277), Japanese Americans (n = 424), Latinos (n = 348), Native Hawaiians (n = 274), and European Americans (n = 386). The established missense risk variant, rs738409, located in PNPLA3 at 22q13, was confirmed to be associated with % liver fat ( P  = 3.52 × 10 −15 ). Also, a novel association of % liver fat with rs77249491 (located at 6q13 between LMBRD1 and COL19A1; P  = 1.42 × 10 8 ) was observed.